IMPLIKASI DESENTRALISASI PENDIDIKAN PADA PENGEMBANGAN PENDIDIKAN ISLAM - Naim, Zaidun (TA'LIMUNA: Jurnal Pendidikan Islam, 2014)
A stronger aspirations for autonomy and decentralization of education can not be separated from the reality of the two conceptual weaknesses in organizing the national education; (1) the national education policy is central and uniform, in which turns ignoring the diversity in accordance with the reality of economy, culture of Indonesian society, (2) national education policy orientation is to achieve the certain targets, such as curriculum targets, in which turn disregarding the effective learning process that is able to reach all areas and students’ potency. This article shows the decentralization of education that significantly contributes the development of Islamic education. With an autonomy of school educational institutions, developing the Islamic education through curriculum development to promote the inculcation of Islamic values to students.